Business model of the depository as integrated reporting element - R. G. Kaspina; L. R . Mukhametshina (Учёт. Анализ. Аудит)
The paper reveals the features of applying the business model of the depository as a tool to improve the efficiency of interaction with stakeholders. The study presents the results of the foreign practice analysis of the business model of integrated reporting. The authors took Foreign organizations carrying out depositary activities as objects of analysis: Standard Bank Group, DBS, Nedbank, Strate. As a result, it allowed to propose a transformed business model for value estimation for interested users. Based on the analysis, the authors substantiated of the process of creating a business model of the depository JSC “Central Depository of the Republic of Tatarstan” and its practical implementation, the necessity of its application in interaction with stakeholders. Using the business model presented in the integrated report, interested users can see the major results of the depository’s activities, the resources and capital used in creating value. Also, they can track the main business processes within the company, draw conclusions whether the results of activities satisfy the interests of certain stakeholder groups. In the course of the research, the authors have used such general scientific methods of cognition as comparison, analysis and synthesis, generalization, systematization, abstraction and modeling.